A SURVEY ON THE FIRST SEMESTER STUDENTS’ MOTIVATION IN LEARNING ENGLISH AT ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Marzuki, Adrian; Dahnilsyah, Dahnilsyah; Syarfi, M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The objective of this research is to find out what type of motivation that first semester students of English Study Program FKIP UR have in learning English. This is a descriptive research that has only one variable applied. In conducting this research, there was 1 class selected with total sample is 40 students, using clustering sampling technique. A set of questionnaire was used to collect the data adapted from AMTB (Attitude/Motivation Test Battery) designed by Gardner (1985). The result of the students’ questionnaire responses shows a percentage score of 97.5% for intrinsic motivation and 92.5% for extrinsic motivation indicating that the students are motivated by their internal and external desire. The results show that they study English because they want to improve their English language skills and also want to use their English for their career.Key Words: Motivation, Learning English